Facile Morphology‐Tunable Preparation of CuS@MoS2 Heterostructures Based on Template Solvothermal Method. Issue 1 (7th January 2020) - Liu, Fangge; Xu, Ruizhi; Hong, Liu; Yang, Zehui; Li, Yunxing; Wang, Chuanxi; Jia, Hongbing; Yang, Cheng
Abstract: Morphology controlling has been considered as an important factor for constructing electrochemical catalysts with excellent catalytic activity as confirmed in recent studies. Herein we report a facile solvothermal method in synthesizing CuS@MoS2 nanocomposite with potentially high catalytic activity, of which different morphologies including nanorod (NR), hierarchical hollow nanosphere (HHNS) and solid nanosphere (SNS) can be simply tuned by solvent polarity and template‐precursor ratio. The morphological variation of these composites is believed as a result of the competition between overall free energy and surface free energy. The alternation in composite morphology finally causes a difference of electrochemical CO2 reduction (CO2 RR) activities among NR, HNNS and SNS, in which a low onset potential (‐0.35 V vs. RHE) and excellent cycling stability can be achieved. Our results demonstrate a large potentiality of CuS@MoS2 nanohybrid to be applied in CO2 RR once its morphology can be controlled. Abstract : We report a facile method in preparing CuS@MoS2 heterostructures, whose morphology can be tuned by co‐solvent polarity and template‐precursor ratio. This morphological variation is caused by the competition between overall surface energy and surface free energy. We prove CO2 reduction activity of our products is potentially dependent to their morphologies.